(untitled) (Huellas, 2015)
During the 19th century the formation of a social basis necessary to strengthen the republican nation constituted a process that had followed a top-down approach promoted by the literate elites who found in real people an obstacle for their own convictions; the “other” that is not accepted or is kept at the margin of modernizing political ideas. These elites will understand the situation in terms of binary oppositions such as “barbarism – civilization”, “possible republic – true republic,” and would enforce the necessary means to overcome them. It was time to found the nation and the elements associated with race, traditions, language and religion were not the proper scaffolding for that foundation. Maybe those are the reasons why the picture of the desert to be populated becomes a metaphor and an explanation for all the evils that prevent the achievement of the desired order. Although the country was characterized by the presence of large extensions of land, those were not desert areas, as they had already been populated, and that native population and their colonial habits blended and became part of that landscape. Consequently, the citizen, according to the former traditions, had to be constructed from scratch. This essay aims at analyzing the image of the desert as a political conception and the invisibilization of the native “other” in the process of building the national state. It is part of the Project “Territorios dinámicos, tramas complejas. Deconstruyendo las relaciones de poder, los actores y las tensiones en diferentes escalas” within the Research Program “Contextos territoriales contemporáneos: abordajes desde la geografía” Resolution Nº 093 – 14 – CD – FCH from UNLPam.